Statistical learning among young and older adults : similar yet different? - Ong, Jia Hoong (2021)
While studies have demonstrated that infants, children, and young adults are capable of statistical learning (SL), it is unclear whether the ability is preserved in older adults and if so, whether they might show a decline. The present study investigates this directly by comparing young and older adults on a standard SL task (word segmentation task). Our results indicate that both age groups did not differ significantly in their overall performance. The two groups, however, differed in their performance on the two distractors used in the task. Furthermore, higher working memory was associated with better SL among older adults, but no such association was seen among young adults. Altogether, this suggests that SL ability is preserved among older adults, but they may be using a different strategy/mechanism compared to young adults, presumably due to age-related decline in the relevant brain structures supporting SL.